Childhood maltreatment, personality disorders and 3‐year persistence of adult alcohol and nicotine dependence in a national sample. (18th February 2016) - Elliott, Jennifer C.; Stohl, Malka; Wall, Melanie M.; Keyes, Katherine M.; Skodol, Andrew E.; Eaton, Nicholas R.; Shmulewitz, Dvora; Goodwin, Renee D.; Grant, Bridget F.; Hasin, Deborah S.
Abstract : Abstract: Background and Aims: Persistent cases of alcohol and nicotine dependence are associated with considerable morbidity and mortality, and are predicted by childhood maltreatment and personality disorders. Our aim was to test whether personality disorders (individually or conjointly) mediate the relationship between childhood maltreatment and the persistence of dependence. Design: Personality disorders, modeled dimensionally, were tested as mediators of the relationship between childhood maltreatment and the 3‐year persistence of alcohol and nicotine dependence in participants in the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) who had current alcohol and nicotine dependence in their baseline interview. Individual personality disorders were assessed in separate models. Then, those that were significant were examined jointly in multiple mediator models to determine their total and unique effects. Setting: A large, nationally representative US survey. Participants: Participants ≥ 18 years who completed baseline and 3‐year follow‐up NESARC interviews who had baseline alcohol dependence ( n  = 1172; 68% male) or nicotine dependence ( n  = 4017; 52.9% male). Measurements: Alcohol Use Disorder and Associated Disabilities Interview Schedule (AUDADIS‐IV) measures of childhood maltreatment, personality disorders and alcohol/nicotine dependence. Findings: Individual models indicated that many personality disorders mediated the relationship between childhood maltreatment and the 3‐year persistence of alcohol and nicotine dependence (each explaining 6–46% of the total effect, P s < 0.05). In multiple mediator models, borderline and antisocial symptoms remained significant mediators, each explaining 20–37% of the total effect ( P s < 0.01). Conclusions: Personality disorder symptoms (especially borderline and antisocial) help explain the association between childhood maltreatment and persistent alcohol and nicotine dependence.